Alantolactone mitigates the elevation of blood pressure in mice induced by angiotensin II by inhibiting calcium channel activation - Ruqiang Yuan; Mingjing Gao; Hu Xu; Qing Liang; Lei Qian; Yali Wang; Houli Zhang; Erjiao Qiang; Weijing Yun (BMC Cardiovascular Disorders)
Abstract Background The dried root of Inula helenium L., known as Inulae Radix in Mongolian medicine, is a widely used heat-clearing plant drug within the Asteraceae family. Alantolactone (ATL), a compound derived from Inulae Radix, is a sesquiterpene lactone with a range of biological activities. However, there is a lack of studies investigating its effectiveness in the treatment of hypertension. The aim of this study is to explore the regulatory effect of alantolactone on blood pressure and its underlying mechanism. Methods and results Network pharmacology analysis suggested that ATL had a potential therapeutic effect on hypertension induced by angiotensin II (Ang II). Subsequently, the results of animal experiments demonstrated that ATL could suppress the increase in blood pressure caused by Ang II. Vascular ring experiments indicated that ATL could inhibit the vascular contractions induced by Ang II, Phenylephrine, and Ca2⁺. Further experiments demonstrated that ATL could inhibit the calcium influx induced by Ang II and increase the expression of pMLC2. Molecular docking experiments showed that ATL had a high binding affinity with L-type Voltage-gated Calcium Channels (VGCC), and vascular ring experiments indicated that ATL could significantly inhibit the vascular contractions caused by the agonists of L-type VGCC. In addition, we also observed that ATL had an ameliorative effect on the vascular remodeling induced by Ang II. Conclusions ATL exerted an antihypertensive effect by inhibiting the activation of L-type VGCC and reducing calcium influx.